ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI JAGUNG (Zea Mays) DI DESA LOSSO KECAMATAN SAMPAGA KABUPATEN MAMUJU - Samsuddin; Laode Ferial Gufran (FAKULTAS PERTANIAN UNIVERSITAS ALKHAIRAAT, 2020)
The purpose of this study was to determine the factors that influence the level of maize production (zea mays) in Losso Village, Sampaga District, Mamuju Regency. The method used in this study to determine the truth of the hypothesis in this study is the method of multiple linear regression data analysis. The results showed that the variable of land area partially has a significant effect on the production of corn farmers in Losso Village, Sampaga District, Mamuju Regency because the probability value is 0.000 <0.05 with the t test result of 4.730. In the regression model the coefficient of X1 (land area) is obtained a value of 1.013, where each additional land area of ​​1%, there will be an increase in production yields of 1.013% assuming the amount of capital and permanent labor. While capital does not have a significant effect on the production of corn farmers, this is evidenced by the results of the t test of (1.168) with a probability value of 0.257.The X2 coefficient of capital (M) is (0.280) which means that every 1% increase in capital will result in an increase in production yields of (0.280)%, with the assumption of fixed land area and labor. The labor variable partially does not have a positive and significant effect on the production of corn farmers as indicated by the t test results of 1.303 with a probability value of 0.208. The X3 coefficient of Labor (TK) is 0.204, where every 1% addition of labor, there will be an increase in production output of 0.204%, assuming land area and fixed capital.